Industry-wide life cycle assessment for improved decision-making: a case study on carbon emissions of petrochemicals - Enking, Jana; Cucurachi, Stefano; Meys, Raoul; Tukker, Arnold (Frontiers in Environmental Science, 2025)
Emission reduction in the petrochemical industry is essential to meet climate targets, as the chemical industry is a major contributor to industrial greenhouse gas emissions. Life Cycle Assessment (LCA) allows for assessing the environmental impacts of alternative production pathways. Still, interlinked industries, such as the petrochemical industry, are difficult to assess in LCA due to the so-called multifunctionality problem. To this end, there are at least two options in LCA to assess industry-wide emissions: a products-wise approach and a product basket-wise approach. Here, we show that optimized technology decisions differ between the two approaches. Optimizing supply chains product-wise leads to 20%–155% higher greenhouse gas emissions compared to a product basket-wise optimization due to (1) a higher amount of by-products, (2) increased raw material need and processing, and (3) suboptimal technology decisions in the supply chain. In contrast to that, a product basket-wise approach is able to adapt in response to changes in demand. Therefore, this approach has advantages over a product-wise assessment due to its possibility to simultaneously assess multifunctional processes. On the other hand, it might also require a complex model and more data.